ADHERENCE TO SELF-CARE IN PATIENTS WITH NEUROGENIC LOWER URINARY TRACT DYSFUNCTION: INSTRUMENT VALIDATION - Cínthia Ferreira Candido; Alessandra Sant’Anna Nunes; Fernanda Henriques da Silva; Livia Fajin de Mello; Advi Catarina Barbachan Moraes; Ellen Marcia Peres (Cogitare Enfermagem, 2023)
Objective: To build and validate the content of the instrument for adherence to self-care for patients with Neurogenic Lower Urinary Tract Dysfunction who perform intermittent self-catheterization as to appearance and content.